DAG HAMMARSKJÖLD AND THE CONCEPT OF PREVENTIVE DIPLOMACY - Dreval , Yuriy (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
Introduction. The present is characterized by the aggravation of contradictions in the international arena, which are increasingly taking the form of armed clashes and military aggression. Under such conditions, the question arises of the ability of the United Nations to ensure the implementation of its statutory goals, primarily in the part where it is about maintaining international peace and security. In this sense, important importance should be attached to positive examples of the participation of this organization in the prevention and resolution of international conflicts, to which the activities of Dag Hammarskjöld as UN Secretary General rightfully belong. Summary of the main results of the study. The main components of Dag Hammarskjöld’s diplomatic activities as UN Secretary-General are systematized. The reasons for the introduction of the concept of preventive diplomacy are revealed, which primarily concerned the inability of the Security Council to reach an understanding on the issues of an adequate response to the escalation of disputes in the international arena. It is confirmed that a kind of "creed" of Dag Hammarskjöld’s political activities was a firm belief in the possibilities of preventive or "quiet diplomacy", that is, approaches to resolving disputes based on negotiations and informal discussions. Conclusions. The position on the essence of the concept of preventive diplomacy in the understanding of Dag Hammarskjöld, which was based on a thorough study of all the causative agents of conflict situations, the involvement of all interested parties in the negotiation process, and at the same time the rejection of any dictates from representatives of major powers, is substantiated.